The Japanese style of marketing: lessons for South Asian managers - Khan, Mumtaz Ahmad (1999)
In this paper, the author recounts the experience of the Japanese style of marketing during his 24-week tenure at Japan's Hosei University and concludes that many lessons can be learnt by South Asian managers from the Japanese. - Reproduced
Keywords: Managers; Marketing